Paradigm Shift in Technological Development of Socio-Economic System in the Context of Digital Transformation - POGODINA, Tatiana Vitalievna; UDALTSOVA, Natalya Leonidovna; FILUSHINA, Alla Vadimovna (Journal of Advanced Research in Law and Economics, 2020)
The world economy is entering the post-industrial technological stage, the basis of which is the fundamentally new technologies (information and communications, bio-, and nanotechnology). Their importance has significantly increased and is reflected in the transformation of the resource base of the modern economic system. These changes are of a civilizational nature, affecting the national economy of any country, and are embodied in a specific technological policy. The research hypothesis is to identify the leading trends in the post-industrial technological structure in the world economy, consisting in the transformation of technology into a basic resource and in knowledge-intensive nature of production that allows extracting additional benefits from international cooperation, creating unique values and providing an increase in economic value added. The purpose of the present study is to identify key trends and assess the potential of technological development of the world and national economy. In this work, statistical, comparative, dynamic, coefficient-based, and structural research methods are used as the main approaches. The article reveals the main trends, problems, and prospects of technological development of the leading economically developed countries and Russia for 2005-2016. The tendencies of the post-industrial mode of production and the most innovative-driven companies are highlighted in each sector of the economy. The authors define the main stages of changing technological structures in the world economy (pre-industrial, industrial and post-industrial), as well as reveal the technologization processes and their characteristic features proving the change of the role of technologies and their transformation into the main factor of socio-economic system development. The effectiveness of technological development is estimated on the basis of a comparative analysis of Russia with the leading countries of the world using indicators of patent applications to the patent office of the country, the proportion of countries in the total number of publications in scientific journals indexed in Web of Science, as well as the proportion of domestic research and development expenditure as a percentage of GDP presented in dynamic mode for 2005-2016. The authors define key characteristics of digital transformation, including stages, segments, dominant technologies, values, and approaches, as well as calculate the level of the economic added value of the country as a target indicator of technologization of the social and economic system. The authors have revealed a direct relationship between the size and nature of the investment and technological development, as well as made conclusion about the need to invest in key sectors of technological development, which is actively progressing in Europe, India, the Republic of Korea, Japan, China, and the United States.